ANALISIS PERBANDINGAN KELULUSAN SISWA SEKOLAH DASAR NEGERI DENGAN JARINGAN SEKOLAH ISLAM TERPADU (JSIT) - Widiastuti; Linora; Hendrizal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the comparison of graduation standards from Public Elementary School and Islamic Elementary School. The unit part of this research is graduation standards and the learning process. The method used in this research is descriptive-qualitative. Basic education is a level of formal education that is mandatory for every child in Indonesia. This level of education aims to provide knowledge, skills and attitudes to students so they can continue to a higher level of education. In Indonesia, there are two types of elementary schools, namely state elementary schools (SDN) and JSIT. These two types of elementary schools have their own characteristics and advantages. Choosing the right elementary school for children must be adjusted to the needs and abilities of each child. Parents need to consider factors that can influence student graduation, such as the quality of education, student motivation, and parental support.